2006
DOI: 10.1093/rheumatology/kep110
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac complications of systemic sclerosis

Abstract: The majority of patients with SSc are believed to have subclinical primary cardiac involvement. Overt cardiac manifestations of SSc are associated with poor prognosis and can be difficult to manage. Primary myocardial disease, i.e. without systemic or pulmonary hypertension and without significant pulmonary or renal disease, is postulated to be due to microvascular ischaemia. Undetected early cardiac manifestations can progress silently to myocardial fibrosis. Symptoms may manifest without warning and can rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 22 publications
2
116
0
1
Order By: Relevance
“…Steen and colleagues (54) demonstrated that thallium perfusion defect scores were the single most powerful predictors of mortality. Myocardial involvement can also be detected by echocardiography and MRI, and may be present clinically in up to 15 to 35% of patients with SSc (53).…”
Section: Myocardial Involvementmentioning
confidence: 99%
“…Steen and colleagues (54) demonstrated that thallium perfusion defect scores were the single most powerful predictors of mortality. Myocardial involvement can also be detected by echocardiography and MRI, and may be present clinically in up to 15 to 35% of patients with SSc (53).…”
Section: Myocardial Involvementmentioning
confidence: 99%
“…Studies confirm the increased risk of cardiovascular diseases in RA [4][5][6][7]. The cardiovascular complications-beside renal and pulmonary ones -are important in the mortality of SSc patients as well [8][9][10].…”
Section: Introductionmentioning
confidence: 81%
“…Treatment options may also vary according to the different types of rheumatic diseases. For instance, immunosuppressive treatment has been shown to be effective in SLE-associated PAH and the response to CCB is poor in rheumatic disease-associated with PAH particularly in SSc (19,27). The response to CCB is poorly defined in other rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%